Community-Based Integrated Child Protection Policy during the Covid-19 Pandemic in Palangka Raya - Sari, Mita (KnE Social Sciences, 2023)
Child Protection is all activities to ensure and protect the children and their rights to live, grow, develop and participate optimally by human dignity, and protect from violence and discrimination, including the most vulnerable groups of violence. The Covid-19 pandemic provides an excellent opportunity for violent behavior against children. Local governments are obliged to guarantee the implementation of prevention of violence against children and support the national policy on prevention, which is implemented through Community-Based Integrated Child Protection. Community-Based Integrated Child Protection is a government program that empowers the community to play a role in the program, thereby being accepted by the community. This article also examines the factors that cause violence against children during the Covid-19 in Palangka Raya and efforts to prevent it. Parents ‘unpreparedness to adapt to changes in routine during the pandemic, changes in children’s learning schemes, and family economic pressure due to the pandemic further exacerbates parents’ psychology. Meanwhile, parents’ knowledge in childcare is relatively minimal- thus, the child is in a position prone to violence. Prevention efforts can be started by strengthening the role and function of the family, then strengthening the role of schools in providing understanding to parents about the importance of educating children without violence, and strengthening the role of religious institutions and community institutions at the local level to provide education on child protection. In addition, family economic empowerment is also important. Keywords: Covid-19; parents’ knowledge; child protection